2020
DOI: 10.34117/bjdv6n4-005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da atividade leishmanicida do látex de Symphonia globulifera

Abstract: Avaliação da atividade leishmanicida do látex de Symphonia globulifera Evaluation of the leishmanicida activity of Symphonia globulifera latex

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In the study by David et al (2019) the researchers found for the latexes of Brosimum parinarioides and Parahancornia amapa the presence of the following phytochemical groups (alkaloids and derivatives of coumarins) and (organic acids, alkaloids, anthraquinones, depside & depsidones, and purines), respectively. Lopes et al (2020) they observed many phytochemical classes present in Symphonia globulifera latex such as saponins, reducing sugars, polysaccharides, phenolics, tannins, flavanones, flavanonols, catechins, xanthones, anthraquinones, depsides & depsidons and coumarins. Gallardo-Vásquez et al (2019) verified the presence of flavonoids, tannins, phenolic alkaloids, carbohydrates, steroids and triterpenes in the latex of J. curcas.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by David et al (2019) the researchers found for the latexes of Brosimum parinarioides and Parahancornia amapa the presence of the following phytochemical groups (alkaloids and derivatives of coumarins) and (organic acids, alkaloids, anthraquinones, depside & depsidones, and purines), respectively. Lopes et al (2020) they observed many phytochemical classes present in Symphonia globulifera latex such as saponins, reducing sugars, polysaccharides, phenolics, tannins, flavanones, flavanonols, catechins, xanthones, anthraquinones, depsides & depsidons and coumarins. Gallardo-Vásquez et al (2019) verified the presence of flavonoids, tannins, phenolic alkaloids, carbohydrates, steroids and triterpenes in the latex of J. curcas.…”
Section: Resultsmentioning
confidence: 99%
“…The advancement of the dissemination of multidrug-resistant bacterial strains has become a worldwide reality and is considered a serious public health problem as it affects not only the hospital community but also the community environment [12]. Reports of multidrug-resistant bacteria have been associated with contaminated environments such as urban rivers [13] and the use of antibiotics in agricultural practices [14]. In addition, within the context of a public health problem, leishmaniasis is neglected, occurring in underdeveloped countries with more vulnerable populations, thereby restricting access to quality health services [15].…”
Section: Introductionmentioning
confidence: 99%
“…with contaminated environments such as urban rivers [11] and the use of antibiotics in agricultural practices [12]. In addition, within the context of a public health problem, leishmaniasis is considered to be neglected, occurring in underdeveloped countries with more vulnerable populations, thereby restricting access to quality health services [13]. Anthropozoonosis is a disease that affects approximately 88 countries and is endemic to Brazil [14].…”
Section: Introductionmentioning
confidence: 99%